The Relationship Between Computational Thinking and Critical Thinking Disposition in Mathematical Problem Solving: Bibliometric Analysis - Perry Zakaria; Ismail Djakaria; Rahmi Moh. Amin; Syafrudin Katili; Majid Majid; Swasti Maharani (STAI Hubbulwathan Duri, 2023)
In the contemporary period, it is imperative for individuals to possess a repertoire of abilities encompassing problem-solving, critical thinking, and computational thinking. In contexts where challenges exhibit a growing level of intricacy and unpredictability. Efforts were made to improve these capabilities. Among them is the integration of learning in this modern curriculum. Mathematics is a branch of science that is expected to be a means for students to hone their abilities. The purpose of this study is to identify trends and research patterns published on the relationship between computational thinking and critical thinking dispositions in solving mathematical problems using bibliometric analysis. In addition, this article also encourages further research to explore various aspects related to the development of sustainable critical thinking and computational thinking in the context of problem-solving in mathematics learning. Data obtained from the Google Scholar database which has been refined with 4 stages (identification, screening, eligibility, and inclusion). The results of the study show that 2020 is the year with the highest and most influential publications because it has the highest h-index value. The research focus related to this topic from 2013-2023 is divided into 4, namely, 1) problem, student, and critical thinking; 2) computational thinking, teacher; 3) mathematics and projects; 4) disposition and science. Project and critical thinking skills are novelty on this research topic.